Genome-wide characterization of bZIP gene family identifies potential members involved in flavonoids biosynthesis in Ginkgo biloba L. - Huan Han (Nature Portfolio, 2021)
Abstract Ginkgo biloba L. is an ancient relict plant with rich pharmacological activity and nutritional value, and its main physiologically active components are flavonoids and terpene lactones. The bZIP gene family is one of the largest gene families in plants and regulates many processes including pathogen defense, secondary metabolism, stress response, seed maturation, and flower development. In this study, genome-wide distribution of the bZIP transcription factors was screened from G. biloba database in silico analysis. A total of 40 bZIP genes were identified in G. biloba and were divided into 10 subclasses. GbbZIP members in the same group share a similar gene structure, number of introns and exons, and motif distribution. Analysis of tissue expression pattern based on transcriptome indicated that GbbZIP08 and GbbZIP15 were most highly expressed in mature leaf. And the expression level of GbbZIP13 was high in all eight tissues. Correlation analysis and phylogenetic tree analysis suggested that GbbZIP08 and GbbZIP15 might be involved in the flavonoid biosynthesis. The transcriptional levels of 20 GbbZIP genes after SA, MeJA, and low temperature treatment were analyzed by qRT-PCR. The expression level of GbbZIP08 was significantly upregulated under 4°C. Protein–protein interaction network analysis indicated that GbbZIP09 might participate in seed germination by interacting with GbbZIP32. Based on transcriptome and degradome data, we found that 32 out of 117 miRNAs were annotated to 17 miRNA families. The results of this study may provide a theoretical foundation for the functional validation of GbbZIP genes in the future.